Sustainability and Green Economy in Developmental Paradigms: A Bibliometric Analysis of Scholarly Trends and Transformations - Muhamad Subhi Apriantoro; Hesti Widyastuti; Afief El Ashfahany; Abdullah Alfikri Murtadla (Universitas KH. Abdul Chalim Mojokerto, 2024)
This study aims to ascertain the trajectory and scope of green economy research inside Scopus-indexed papers. This research uses bibliometric analytic methodologies to investigate all publications cataloged in the Scopus database about the green economy within a sustainable development framework spanning 1990 to 2023. The data collected was analyzed using both Excel and r/r studio software. Vosviewer is a software tool that enables the simultaneous visual study of keyword occurrence and document extracts. The researcher identified 859 publications that align with the designated role, subject matter, and specified criteria. The findings of this study reveal a yearly growth rate of 17.98%, with the highest number of publications observed in the field of environmental science in the year 2022. China is the nation that exhibits the highest level of scholarly output in terms of publications associated with the Chinese Academy of Sciences. Lyulyof, o. He is widely recognized as a highly prolific author within the field of the green economy. The bibliometric analysis conducted was restricted to the utilization of Scopus data. This study did not consider other national and international datasets. This study offers a concise survey of the literature available to scholars engaged in academic research and presents suggestions for future research endeavors.